The detection of K88, K99 fimbrial antigen and enterotoxin genes of Escherichia coli isolated from piglets and calves with diarrhoea in Indonesia - Supar . (Indonesian Center for Animal Research and Development (ICARD), 1996)
Enterotoxigenic Escherichia coli (ETEC) strains cause diarrhoeal disease in piglets and calves in Indonesia. These strains possess two virulence factors namely attachment and enterotoxin antigens . These factors could be detected phenotypically and genetically. Haemolytic Escherichia coli (E coli) isolates possessing K88 fimbrial antigen associated with 0-group 108 and 149. They were positive for K88 gene and demonstrated their ability to produce heat labile enterotoxin (LT) and genetically were all positive for LT gene . Seventeen isolates ofE coli K88 which associated with 0-group 149 were positive forSTb gene, other O-serotypes were negative . Ten isolates of Ecoli K88 which associated with 0-group 108 possessed K88, K99, LT and STa genes, but negative for STb gene . However, phenotypically the K99 antigen and STa toxin were not expressed under laboratory conditions, the reason was not well understood . E. coli K99 strains isolated from calves wit h diarrhoea were all associated with 0-group 9 and produced STa toxin when tested by suckling mousse bioassay. The E. coli K99 calf isolates were all hybridized with K99 and STa gene only . It is likely that K99 gene is associated with STa gene . The DNA hybridization technique is more convenience to be used for confirmation diagnosis of colibacillosis, however, not all veterinary laboratories could perform these tests . Keywords: Excherichia coli, probe, gene detection, virulence determinant